Health Coverage Tax Credit Authorized by the Trade Act of 2002. (U.S. Congressional Research., 2007)
Provides overview of the Trade Act of 2002 health coverage tax credit (HCTC), which applies to the health insurance costs of individuals receiving trade adjustment assistance or benefits from the Pension Benefit Guaranty Corporation. Discusses HCTC eligibility and insurance plans qualified for HCTC coverage; HCTC implementation, including Federal grants to States to support implementation; issues in HCTC design and implementation, including effectiveness, equity, and efficiency issues; and HCTC-related legislation in the 110th Congress.